An Efficient Onboard Quantization Strategy for Multi-Channel SAR Systems - Martone, Michele; Villano, Michelangelo; Younis, Marwan; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2018)
Multi-channel SAR systems allow high-resolution imaging of a wide swath and represent an attractive solution for present and next-generation SAR mission concepts. However, their operation requires the downlink of a huge amount of data: in addition to the intrinsic data requirement related to resolution and swath, in fact, a pulse repetition frequency (PRF) higher than the processed Doppler bandwidth is usually selected. A convenient data reduction strategy is therefore proposed, which exploits the correlation between samples by performing variable-bit quantization of the data after a block transformation of the multichannel SAR data, e.g., an FFT. Simulations show that this allows reducing the data volume while keeping the same performance at the cost of a modest onboard processing effort.
Keywords: Multichannel Synthetic Aperture Radar (SAR); Quantization; Data Reduction